THE RELATIONSHIP BETWEEN KNOWLEDGE AMONG WOMEN OF REPRODUCTIVE AGE ABOUT BREAST SELF-EXAMINATION WITH EARLY DETECTION OF BREAST CANCER AT KELURAHAN SINDANG BARANG, BOGOR : HUBUNGAN PENGETAHUAN WANITA USIA SUBUR (WUS) TENTANG PEMERIKSAAN PAYUDARA SENDIRI (SADARI) DENGAN DETEKSI DINI KANKER PAYUDARA DI KELURAHAN SINDANG BARANG KOTA BOGOR - Ami Oetamiati Wiharjo (Jurnal Ilmiah Wijaya, 2018)
Background :In Indonesia based on Globar Burden of Cancer database, breast cancer is the most cancer who suspecting women reached (26 per 100.000), followed by uterus cancer (16 per 100.000). Based on the Hospital Data Information System (SIRS) in 2007 showed that the incidence of breast cancer reaches 21,69% higher than the figure of cervical cancer 17%. Objective : Determined the relation of knowledge about women of childbearing aware with the early detection of breast cancer in Kelurahan Sindang Barang Bogor. Methods : This reaserch is a type of analytic descriptin with cross sectional design research. Methods of sampling in this research tecnique sample random sampling number of 97 people. The collection of data abtained through thr distribution of questionnaires in the form of the now closed. Result : Based on knowledge about BSE largely WUS 62 respondents (63.9%) and a fraction less knowledgeable 10 respondents (10.3%) good knowledge. Early detection of breast cancer in WUS majority of 55 respondents (56.7%) positive early detection and fraction 42 respondents (43.3%) negative early detection. Relations WUS knowledge about BSE with early detection of breast cancer is the most of 62 respondents (63.9%) less of knowledge among 35 respondents (36.1%) negative early detection and 27 respondents (27.8%) are positive early detection. The test results obtained statistical p value = 0.002 which means there is a significant relationship of two variables. Summary : There is a relatioship between knowledge among women of reproductive age about breast self-examination with early detection of breact cancer at keluarahan Sindang Barang Bogor2015. Suggestion : This research are usefull for healthcare to outreach on knowledge among women of reproductive age about breast self-examination with early detection of breact cancer, so that the women of reproductive age can be find out the information about breast cancer itself.